The roles of EFL Teachers in Promoting Learner Autonomy - Putu Wiraningsih; N.L.P.E.S. Dewi (Jurnal Pendidikan dan Pengajaran, 2020)
This study is a descriptive-qualitative study which aimed to describe the roles of EFL teachers in promoting learner autonomy. Four EFL teachers in seventh grade junior high schools were selected as the subject of this study. The data were collected through questionnaire and observation techniques. In collecting the data, two kinds of instruments were used, namely, questionnaire and observation sheet. The result of this study revealed that in promoting learner autonomy, the teachers perform the roles as facilitator, counsellor, resource and manager/organizer. Considering the result of the study, the teacher should involve their students in the decision making process of learning activity, not only in selecting the technique or approach, but also in all aspects of learning process such as selecting objectives of the course, managing classroom and selecting the materials. Schools also need to support their teachers in developing innovative strategy especially in promoting learner autonomy. The schools should offer teachers with professional development programs on learner autonomy such as following workshops. For further researchers, considering the challenges met by the EFL faced by the EFL teachers in promoting learner autonomy is needed.